Human Rights in the Quran: Addressing Criticisms on Freedom of Religion and Apostasy - Muhammad Khalid Rehmat; Munawar Hussain (Journal of Religion and Society, 2025)
The paper discusses Quranic teachings and compatibility with contemporary standards of human rights as regards to freedom of religion and apostasy in Islam. The critics tend to point out the seeming inconsistencies between Quranic passages that advocate religious freedom (e.g. 2:256, No compulsion in religion) and the passages that are interpreted as restrictive (e.g. 9:29, Fight disbelievers). The paper answers these objections by contextual interpretation of Quran, classical commentary (Tafsir) and modern scholarship, and points out the difference between theological principles and historical juristic applications. The major Quranic topics such as the dignity of a human being (17:70), justice (5:8), and voluntary faith are demonstrated to go in line with the normative human rights, whereas the traditional laws of apostasy are claimed to represent political conditions during the middle ages rather than unchangeable decrees. The article discusses the idea of reconciliation of Sharia with modern pluralism through reformist solutions such as Maqasid al-Sharia (higher objectives of Islamic law) by giving examples of Tunisia, Morocco and Indonesia. Obstacles like that of traditionalism in following the juristic consensus (ijma) and the clash of secular and Islamic systems are discussed and the way legal, educational and scholarly changes are to be brought to promote intra-Muslim dialogue and interpretations which are in compliance with human rights are highlighted.. Keywords: Human Rights, Quran, Freedom of Religion, Apostasy, Maqasid Al-Sharia, Islamic Jurisprudence, Reform, Pluralism, Contextual Analysis